Mensch-Technik-Interaktion in medikalisierten Alltagen - Wöhlke, Sabine; Palm, Anna (Universitätsverlag Göttingen, 2018)
Increasing mechanization is profoundly changing our social areas of life as well as cultural orders and knowledge systems. Concepts of health and illness are also permeated by such technology. A variety of communication techniques are used in the medicalized everyday life: new biotechnologies are combining with home and life techniques; for a long time, a digital self-measurement market has been developed by application techniques; such as, Smartphones, data glasses and Smartwatches. In the meantime, it is easier and faster to operate medical devices and systems. In addition, the data obtained can be exchanged and analyzed faster and faster. A so-called assisted health technology and new information and communication options make the interface between human and machine blurred. The anthology addresses fundamental social, cultural and ethical questions of human-technology interaction and, from a cultural and social scientific research perspective, addresses the question of how technology alters everyday life, cultural orders and knowledge systems.